Investigation of aerosol effects on the Arctic surface temperature during the diurnal cycle: part 2 – Separating aerosol effects. (12th May 2017) - Stofferahn, Eric; Boybeyi, Zafer
ABSTRACT: Temperature changes in the Arctic due to anthropogenic climate change are larger in magnitude than those at lower latitudes, with sea ice extent and thickness diminishing since the dawn of the satellite era. Aerosols play a role in determining the changes to the Arctic surface temperature. While Part 1 of this two‐part study investigated the changes in Arctic surface temperature due to the total aerosol effect, in Part 2, the total aerosol effect is separated into the changes caused by the aerosol direct effect, the aerosol semi‐direct effect, and the aerosol indirect effects through the use of additional Weather Research and Forecasting Chemistry (WRF‐Chem) runs. While Part 1 of the study showed that aerosols may have both a cooling and warming effect, largely depending upon the time of day and aerosol concentration, Part 2 of this study shows that the indirect effects are the dominant component of the total aerosol effect on the cooling and warming of the Arctic surface temperature throughout the diurnal cycle. It is also shown that the size distribution of aerosols is important, as smaller aerosols dominate the aerosol indirect effects. The aerosol direct effect contributes to cooling in the region, while the semi‐direct effect is negligible.